Evaluasi Penanganan Genangan Air Di Underpass Makamhaji Kabupaten Sukoharjo - Fajar Utomo, Fibrian; , Ir. Achmad Karim F. M.T; , Gurawan Djati Wibowo, ST., M.Eng (2017)
Makamhaji is one of the villages in Sukoharjo, Central Java. In Makamhaji, here is an underpass which is an alternative route connecting Solo to Sukoharjo. In 2015, Makamhaji underpass often contained water (flooding). From the mentioned problem, a research conducted to know the flood evaluation of Makamhaji underpass. This research used documentation and observation methods. Documentation method is collecting past available data such as percipitation and catchment area data. Observation method is observing and recording the condition of the underpass, such as the pump, pipe and reservoir used for water in Makamhaji underpass. The reservoir of Makamhaji underpass measuring 3x2,5 square meter with a depth of 2,5 meters with 18,75 meter cubic of volume. After calculating the volume of flood that has a return period of 50 years, it has 9,937 meter cubic. Therefore, the reservoir can contain the volume of flood. The water that swamp the underpass not only caused by flood, but also from groundwater seepage. But the seepage that happens on the floor of underpass (ground water) is smaller than the flood flow surface itself, which is only 0,2 percentage. The pump used on the underpass of Makamhaji is 7,5 horse power. The time needed for the pump to pump out the water on the reservoir is 17.917375 minutes. Based on the evaluation of a flood that happened on December 12, 2015, the flooding on Makamhaji underpass is due to the possibility of jammed pump and the garbage that is blocking the drainage channel. In this research, channel 5 and 6 are failed to drain the flood debit into the reservoir. Redesign is needed so the channels able to drain the flood debit into the reservoir. Key words: underpass, reservoir, the volume of flood, submersible pump